KEEFEKTIFAN METODE SPONTANEOUS GROUP DISCUSSION TERHADAP KETERAMPILAN BERBICARA TEKS LAPORAN HASIL OBSERVASI SISWA KELAS VIII SMP - Fitri Rosalinda; Burhan Sidik; Tanzilia Nur Fajriati (STKIP Subang, 2026)
Speaking skill is one of the essential language competencies that students should master in Indonesian language learning. However, students' ability to present observation report texts orally remains relatively low. This study aimed to analyze the effectiveness of the Spontaneous Group Discussion (SGD) method in improving the speaking skills of eighth-grade junior high school students in presenting observation report texts. The research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The participants consisted of an experimental class taught using the SGD method and a control class taught through conventional learning. Data were collected through speaking performance tests administered before and after the treatment. The data were analyzed using descriptive statistics, normality tests, homogeneity tests, and the Mann–Whitney test. The findings indicated that the speaking skills of students in the experimental class improved more significantly than those in the control class. Furthermore, the hypothesis test confirmed a significant difference between the two groups after the treatment. Therefore, the Spontaneous Group Discussion method was proven effective in improving students' speaking skills in presenting observation report texts.